(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The Impact of Modern Agriculture on Rural development deals with the role of agriculture in rural development and analyzes the interplay between social and technological aspects of rural development. The study focuses to find out the extent of adoption of better inputs of farming and the magnitude of socio-economic benefits of agricultural modernization for different size group of agriculturists. The study was conducted for farming community of five villages covered by the intensive agriculture development program. The author finds that the adoption is not up to the expected level because of the objective factors influencing the ecology of cultivation and the subjective condition, values and attitudes of the cultivation